The impact of local tax revenue on society welfare - Marfiana, Andri; Prabowo, Sakti; Wijaya, Suparna; Irawan, Ferry (Educoretax, 2024)
Regional taxes are one of the pillars of state revenue. Regional taxes have a strategic position both for financing development in the regions and regulating community life in the regions. This study aims to investigate the effect of regional tax revenues on public welfare in Indonesia. This study uses a quantitative method with secondary data obtained from the Central Statistics Agency for the period 2019 - 2021. The power taken includes regional tax variables, education level, number of poor people, and availability of basic health facilities. The test results show the following findings. First, regional tax revenues have the potential to encourage socio-economic development but the impact is highly dependent on the effectiveness of budget allocation and management. Second, regional tax revenues have not had a significant impact on reducing the number of poor people. However, these results emphasize the importance of an integrated approach. Third, the development of basic health facilities depends more on the Special Allocation Fund than regional tax revenues.